Gestão do trabalho na saúde : com a palavra, atores da estratégia saúde da família do município de Linhares -ES - Felsky, Camila Nogueira (2013)
This dissertation discusses labor management in the Family Health Strategy, from the meanings attributed by managers and workers to the policies and actions in this field, as well as their implications for workers in family health teams. This is an exploratory, descriptive, qualitative study, conducted in Linhares, Espírito Santo, related to municipal management in the period 2009-2012. Semi-structured interviews were conducted with three managers of the municipal health office and focus groups were carried out with twenty-four workers of three family health teams (community health workers, nursing auxiliary, nurses and physician). Data analysis was performed using the content analysis technique proposed by Bardin (2011). From this analysis, seven categories emerged: knowledge about labor management policies; labor links status; employment relationship; plan of careers jobs and salaries and remuneration; work infrastructure; workload; education and training. It was observed limited knowledge about the labor management policies formulated by the Brazilian Ministry of Health, by both managers and workers. In general, there was little appreciation of initiatives aimed at improving working relations, conditions and processes of teams. The effects of this scarce investment were felt by the workers, who reported various dissatisfactions and insecurities. Thus, despite the increase in the formulation of policies for the field of the labor and education management in health for the Brazilian National Health System at the federal level, the research points to the need for studies that assist in the expansion of tools that promote higher visibility and knowledge of these policies, whereas in the city studied they are not known, which hinders their implementation. Furthermore, although the respondents recognize the importance of labor management for favoring a major role of those involved in the production of health, it turns out that this recognition is still more on the level of speech and is not reflected on the municipal political agenda